VIRAL MARKETING: A BIBLIOMETRIC APPROACH TO EXPLORE RESEARCH NOVELTY - Nurafni Rubiyanti; Mahendra Fakhri; Aznul Fazrin bin Abu Sujak (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2023)
In this article, we evaluate works on electronic viral marketing using bibliometric analysis and systematic review in this paper. Our data reveal that there has been a substantial increase in research publications during the previous two decades. Viral marketing, social media, and word-of-mouth are some of the hottest subjects in this field. We inferred many issue clusters from this research, including influence, attitude, social network, and electronic word-of-mouth. This article also explores the implications and potential future directions of the research.